The tension between technology and market demands in the development of digital platforms - Kolbinger, Martin (My University, 2022)
There are already many established digital platforms on the market, such as ebay, Amazon Marketplace, and Android. In addition to these existing and successful platforms, other new digital platforms are also being developed. During such a development, various technology- and market-related demands are placed on these digital platforms, both on the finished software product and on the development process. These technology- and marketrelated demands are often in conflict and create tensions that need to be resolved during the development process. This thesis investigates these demands and provides an approach how these tensions between technology- and market-related demands can be solved. Firstly the different demands were reviewed and by analyzing them, they could be reduced to the three main requirements "fast", "good", "cheap", which are usually in competition in a software development project and thus create tensions. With the goal of resolving the tension between technology and market demands in digital platforms, a literature review and a case study in the form of expert interviews were conducted. Through these two methods, eight different approaches were identified on how these tensions can be resolved. All these approaches could be traced back to the central element of knowledge and thus the understanding of all technology and market demands. This central element leads to the conclusion that in order to solve tensions between technology- and market-related demands, it is essential to possess or acquire the necessary knowledge. However, there is no patent remedy for acquiring the knowledge or organizing the knowledge so that it is available and accessible at the right time in a project for developing a digital platform. This leads to the conclusion that each development must find its own combination of measures for knowledge acquisition and organization.